2016
DOI: 10.1186/s12917-016-0917-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of regionally-specific immunotherapy for the management of canine atopic dermatitis

Abstract: BackgroundCanine atopic dermatitis is a common pruritic skin disease often treated with allergen immunotherapy (AIT). AIT in dogs traditionally begins with attempting to identify clinically relevant environmental allergens. Current allergen testing methodologies and immunotherapy techniques in dogs are not standardized. Immunotherapy with a mixture of allergenic extracts selected based on regional aerobiology rather than intradermal tests or serum IgE assays has been described. The objective of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…28,29 Much of our knowledge and use of allergens in veterinary patients is extrapolated from the human field. 26 Veterinary labora tories performing serum IgE testing within the USA divide regions into aerobiological zones and select aller gens implicated in that zone based on many factors; 30 however, the methods for detection of IgE and the num bers and types of allergens between laboratories varies greatly. 31 For example, serum from cats that were experi mentally sensitized to either house dust mite or Bermuda grass allergen were divided and sent as blinded samples to two commercial laboratories with different methods for IgE testing, with dramatically discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Much of our knowledge and use of allergens in veterinary patients is extrapolated from the human field. 26 Veterinary labora tories performing serum IgE testing within the USA divide regions into aerobiological zones and select aller gens implicated in that zone based on many factors; 30 however, the methods for detection of IgE and the num bers and types of allergens between laboratories varies greatly. 31 For example, serum from cats that were experi mentally sensitized to either house dust mite or Bermuda grass allergen were divided and sent as blinded samples to two commercial laboratories with different methods for IgE testing, with dramatically discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…intramuscularly ( Toyohara et al., 2013 ). On day nine, under general anesthesia induced by pentobarbital (50 mg/kg IP) ( Zatroch et al., 2017 ), blood was withdrawn by retro-orbital puncture, serum was separated and stored at −80°C until use, and animals were euthanized by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…3 6-8 Some retrospective and non-controlled studies have suggested that ASIT is efective in controlling the clinical signs of AD in 50-80 per cent of treated dogs. [9][10][11][12][13][14] However, it is still diicult to understand how and why some dogs show an excellent response to ASIT, whereas others show little or no improvement after months of treatment.…”
Section: Introductionmentioning
confidence: 99%